Evaluating the Impact of the Global Financial Crisis on the Stock Markets of BRICS Countries - Singh, Amit Kumar; Shrivastav, Rohit Kumar (Indian Journal of Finance, 2018)
The global financial crisis of 2007 - 2008 left every economy in a state of shock and also increased the volatility in the markets across the world since internationalization of capital markets not only gives an opportunity to investors to invest their money in their own country, but also the country of their choice too. Therefore, during the period of crisis, international investors tried to diversify their investments in more promising countries. BRICS countries, being a global market hub, have been growing faster than the world growth rate and saw more investment movements during and after this period. The present study attempted to evaluate the impact of the financial crisis on BRICS countries’ stock markets. The impact was examined by analyzing the growth rate of BRICS countries’ stock markets index prices in the pre and post crisis period (from 2002-2015) with the application of a dummy based model considering time as a dummy. Our results revealed that the BRICS were subject to a spillover effect during and following the financial crisis. Brazilian, Russian, and Chinese markets had a negative growth in index prices and captured more volatility and thereby, increased the risk of investors ; whereas, the Indian and South African markets captured some degree of shock in the beginning of the crisis, but showed a positive momentum. We further found that in the long run, these nations recovered successfully from the crisis as they invited more foreign investments in their markets to recover.